2021
DOI: 10.3389/fonc.2021.602712
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Signaling Pathway Responses to rhIL-6 Intervention Before Lobaplatin Treatment in Osteosarcoma Cells

Abstract: Lobaplatin is a third-generation platinum-based antineoplastic agent and is widely used for osteosarcoma treatment before and after tumor removal. However, treatment failure often results from lobaplatin drug resistance. In our study, we found that SaOS-2 and SOSP-9607 osteosarcoma cells became less sensitive to lobaplatin after treatment with exogenous interleukin (IL)-6. Quantitative proteomic analysis was performed to elucidate the underlying mechanism in SaOS-2 osteosarcoma cells. Cells were divided into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…One of the possible reasons may be the difficulty in obtaining control tissues for some types of sarcoma and therefore the lack of precise data. In our previous study, we found that a high level of FUBP1 could confer lobaplatin resistance in osteosarcoma cell lines, which resulted in poor outcomes ( Wang et al, 2021a ). We also compared the expression of the FUBP1 protein in platinum-resistant and platinum-sensitive specimens, and a significant difference was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible reasons may be the difficulty in obtaining control tissues for some types of sarcoma and therefore the lack of precise data. In our previous study, we found that a high level of FUBP1 could confer lobaplatin resistance in osteosarcoma cell lines, which resulted in poor outcomes ( Wang et al, 2021a ). We also compared the expression of the FUBP1 protein in platinum-resistant and platinum-sensitive specimens, and a significant difference was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the noncoding RNAs LCAT3 and circACTN4 can interact with FUBP1 and thereby activate c-MYC in lung cancer and breast cancer respectively ( Qian et al, 2021 ; Wang et al, 2021b ). Our team has focused on the multifunctional FUBP1 protein and has reported on the links between FUBP1 and chemoresistance in human osteosarcoma cells ( Wang et al, 2021a ). However, no pan-cancer analyses have been conducted to explore the relationship between FUBP1 expression and various cancer types based on clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations highlight that FUBP1 could be used as a therapeutic candidate for patient‐tailored treatment alongside chemotherapy for different tumors. Our previous research found that FUBP1 could decrease the sensitivity of osteosarcoma cells to lobaplatin 19 . However, the specific mechanisms and signaling pathway remain unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous research found that FUBP1 could decrease the sensitivity of osteosarcoma cells to lobaplatin. 19 However, the specific mechanisms and signaling pathway remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting IL-6 could be an effective strategy for overcoming stroma-induced chemotherapeutic resistance to tocilizumab in gastric cancer [ 5 ]. Additionally, according to previous studies, IL-6 is involved in resistance to chemotherapy in osteosarcoma cells in vitro [ 6 8 ]. However, to date, specific changes in phosphoproteins at the post-translational level have not been discovered.…”
Section: Introductionmentioning
confidence: 99%